Patient experiences with group consultations when treated with semaglutide for obesity: a qualitative case study in a Danish general practice - Jan Erik Henriksen; Jens Søndergaard; Elisabeth Assing Hvidt; Rasmus Dahl-Larsen; PR Jakobsen (BMJ Open)
Objective In this case study conducted in a Danish general practice, we aimed to explore how patients with obesity experience a novel treatment approach: group consultations (GCs) for weight loss, lifestyle changes and semaglutide treatment. To receive semaglutide treatment, patients were required to participate in GCs focused on lifestyle changes.Design A qualitative study design comprising individual, semistructured interviews was used. Patients were asked to reflect on and describe their past experiences with participating in GCs. Thematic analysis was used as an analytical strategy.Setting A general practice located in a larger city in the Region of Southern Denmark.Participants 12 patients (eight women and four men) with obesity, aged between 27 years and 69 years, who met the Danish obesity treatment criteria for semaglutide (body mass index over 30 kg/m2 or over 27 kg/m2 with comorbidities), were included. Data were collected from 1 November 2023 to 31 January 2024.Results Before attending GCs, patients were worried about sharing personal information with other patients and losing their confidentiality. They also feared being judged by the others in the group, possibly due to previous experiences of stigmatisation. However, after participating in GCs, patients reported positive experiences with peer sharing, had no issues with confidentiality and found the consultations beneficial. Most patients indicated a preference for GCs over one-on-one consultations in the future.Conclusions Despite initial concerns about confidentiality and stigmatisation, patients ultimately had positive experiences and gained valuable peer support during group GCs in general practice. Various aspects of the group design, such as the hybrid consultation format and the role of the facilitator, may impact the effectiveness of peer support and influence patients’ overall experience of GCs.